Peak Expiratory Flow Rate and Its Anthropometric Correlates in Healthy Urban Indian School Adolescents Aged 12-17 Years in Western India - Gatecha, Eva; Reddy, Bhargav M (National Journal of Medical Research, 2025)
Background: Peak Expiratory Flow Rate (PEFR) is a simple, non-invasive measure of pulmonary function, influenced by anthropometric factors. Establishing normative PEFR values for adolescents is crucial for assessing respiratory health, particularly in diverse populations like India. This study aimed to determine normative PEFR values in healthy urban Indian school adolescents aged 12-17 years and evaluate their correlations with anthropometric variables, including height, weight, body mass index (BMI), body surface area (BSA), mid-upper arm circumference (MUAC), and chest circumference. Methods: A cross-sectional study was conducted among 1,060 adolescents (530 boys, 530 girls) at a private school in Surat, Gujarat, from August 2018 to February 2020. PEFR was measured using a Mini-Wright Peak Flow Meter, and anthropometric data were collected using standardized instruments. Pearson correlation coefficients and multiple regression models assessed relationships between PEFR and anthropometric variables. Results: Mean PEFR was 344.98 ± 45.35 L/min for boys and 323.26 ± 42.31 L/min for girls, increasing with age. PEFR showed strong correlations with height (r = 0.999), weight (r = 0.990), BMI (r = 0.954), BSA (r = 0.997), and chest circumference (r = 0.979) (all p < 0.001), but a weaker correlation with MUAC (r = 0.229, p <0.001). Height was the strongest predictor in regression models. Conclusion: Normative PEFR values were established, with height as the primary determinant. These region-specific standards aid in assessing adolescent respiratory health.